Improving medicines reconciliation rates at Ashford and St. Peter's Hospitals NHS Foundation Trust - Doolub, Reshmee (BMJ Qual Improv Rep, 2017)
Medicines reconciliation is integral to patient safety, symptom control and reducing patient anxiety. During a 3-month period on the respiratory ward at St. Peter's Hospital, 54% of drug charts were not reconciled with pre-admission medicines at the point of discharge for admissions up to 17 days. Only 18% were reconciled within 24 hours of admission. 50% of drug charts were missing 0-2 pre-admission medicines and 50% were missing 3-5 pre-admission medicines. The most common medicines that were not reconciled included topical applications which included eye, ear, nasal and skin applications (14%); vitamins i.e. vitamin B12 and thiamine, analgesia, PRN inhalers (11% individually); antidepressants and lipid regulators (6% individually); amongst a range of other medications including antiplatelets, calcium channel blockers, ACE inhibitors and diuretics. Two interventions were carried out to improve the rate of medicines reconciliation onto hospital drug charts with pre-admission medicines. These were: 1) a green sticker placed in the medical notes by the pharmacist when drug charts were incomplete, which required a date and signature from the doctor when the drug chart had been reconciled 2) the placing of the loose medicines reconciliation record (a list of pre-admission medicines retrieved from a reliable source usually by the pharmacist) to the front of the drug chart. These measures were designed to alert the doctors that the drug chart was incomplete. After 2 PDSA cycles, the results showed positive outcomes. In 75% of the cases where the interventions were used, medicines reconciliation was complete at the point of discharge with 34% of drug charts reconciled within 24 hours of admission. Of the 25% of drug charts that were not reconciled despite the use of the interventions, 100% of them were missing 0-2 medicines however 0% were missing 3-5 medicines. This highlights that the interventions were effective in improving the rates of medicines reconciliation.